2023
DOI: 10.3126/jaim.v12i1.56675
|View full text |Cite
|
Sign up to set email alerts
|

A study on demographic and clinicopathological characteristics of severe acute pancreatitis in a tertiary-level intensive care unit in Nepal

Kishor Khanal,
Saroj Poudel,
Anup Ghimire
et al.

Abstract: BACKGROUND AND AIMS Severe acute pancreatitis can have serious consequences and a high mortality rate and may necessarily require intensive care unit admission. This study is to describe the demographic and clinicopathological characteristics of severe acute pancreatitis (SAP) in a tertiary-level intensive care unit (ICU). METHODS The study was designed retrospectively with a diagnosis of severe acute pancreatitis (SAP) admitted to the tertiary-level adult ICU “between” January 2019 to December 2022. RESULTS A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…At the time of presentation, all patients had abdominal pain, whereas 44 (61%) and 22 (30%) had vomiting and fever, respectively. These findings are consistent with those reported by Khanal et al and Ramu et al [14,15].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…At the time of presentation, all patients had abdominal pain, whereas 44 (61%) and 22 (30%) had vomiting and fever, respectively. These findings are consistent with those reported by Khanal et al and Ramu et al [14,15].…”
Section: Discussionsupporting
confidence: 94%
“…Although many studies recommend ERCP within 72 hours of an acute gallstone-induced pancreatitis attack and have shown that it decreases complications [11], this study's participants were managed conservatively because ERCP facilities were unavailable. However, 23 (31.9%) participants with complications improved, whereas 47 (65%) had uneventful recoveries and only two (2.7%) died of complications that caused multi-systemic failure, which is consistent with the findings by Khanal et al [14].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations